THE IMPACT OF INSOMNIA ON THE MENTAL AND EMOTIONAL HEALTH OF STUDENTS (JOURNAL OF ANALYTICAL SYNERGY AND SCIENTIFIC HORIZON, 2025)
Sleep disorders can have a significant impact on a person's overall health and well-being. As future doctors, it is important to investigate sleep issues in order to better understand how they affect our ability to provide quality care for patients. This information could also be used to improve patient treatment and ensure patient safety. Sleep deprivation can lead to negative effects on doctors' cognitive function, decision-making abilities, and increased risk of burnout. By addressing insomnia in health care professionals, we can prevent burnout and promote well-being among doctors, leading to reduced errors and improved patient outcomes.